FINTECH ECOSYSTEM IN VIETNAM - Dang, Anh (My University, 2018)
This paper reviews current status of the fintech ecosystem in Vietnam through the lens of critical actors of a fintech ecosystem and in comparison with Singapore. It is to find out which actors are for setting up an ecosystem now and maintaining a healthy ecosystem in the future. The intention in doing so is to assess the role of each actor and reflect the relationship among them. The final aim is to understand the emergence of fintech ecosystem in Vietnam, from which to suggest some ways to develop the ecosystem. This study adopts theory of Nicoletti (2017) and Adner and Kapoor (2016). From Nicoletti (2017), five actors of a fintech ecosystem are recognized. They are demand,talent, solutions, capital and policy. All individuals, businesses and financial institutions have demand for modern financial products and services, originating from prevalence of technology in nearly all aspects of life now. Good academic performance at school shown by PISA result is not enough to bring excellence to technology and financial institutions. Talent of technology places has little been mentioned. Some banks are incorporating fintech in their operations. Fintech entrepreneurs are generally potential but they need to be better equipped with expertise knowledge and more innovative. Solutions from academic resources are almost zero, from fintech companies not diverse,from crowdsourcing too tiny. The collaboration between fintech companies and banks is bringing advantages to both parties. Angel investors and IPO are now not a viable option for fintech companies in Vietnam. Venture capital is easier to reach. Both local and foreign venture funds are showing interest in Vietnam’s fintech. Policy is still more in paper than in practice. After discussing the role of each actor and their correlation, the discussion moved to recommendations drawn from the theory of Adner and Kapoor (2016). Based on their framework, Vietnam is now in the first stage, in which traditional financial services do not completely meet growing customer need while fintech started to be paid special attention to. A sensible approach is to devote huge effort to fintech. This is proven in reality of Singapore. Fintech companies are in the heart of their ecosystem and all the actors are working hard. Some lessons can be learned from Singapore are: focusing on fintech companies – this is also emphasized in Nicoletti (2017)’s framework, policy offering more incentives to investors in fintech companies and supporting to improve quality of talent and solutions.
Keywords: fintech ecosystem, Vietnam